The Inhibitory Effect of PIK-75 on Inflammatory Mediator Response Induced by Hydrogen Peroxide in Feline Esophageal Epithelial Cells - Jun Yeong Jeong; Yeon Joo Lee; Jeong Hoon Han; Sun Young Park; Kwang Woo Hwang; Uy Dong Sohn (Hindawi Limited, 2014)
Isoform-selective inhibitors of phosphoinositide 3-kinase (PI3K) activation have an anti-inflammatory effect by reducing proinflammatory cytokines. Cultured feline esophageal epithelial cells (EEC) of passages 3~4 were treated with hydrogen peroxide and PIK-75. The cell viability was measured by a MTT incorporation assay. The distribution of PI3K isoforms, p-Akt, IL-1β, and IL-8 was inferred from Western blots. The release of IL-6 was determined by ELISA. The cell morphology was not considerably different from nontreated cells if the cells were pretreated with PIK-75 and treated with 300 μM hydrogen peroxide. The density of p110α of PI3K was increased, but that of other types was not affected after the treatment with hydrogen peroxide. The density of p-Akt, when the cells were exposed to PIK-75 and hydrogen peroxide, was diminished dose dependently more than that of hydrogen peroxide treatment only. The decrease of p-Akt showed an inhibition of PI3K by PIK-75. PIK-75 dose dependently reduced the expression of IL-1β, IL-8, and the level of IL-6 compared with hydrogen peroxide treatment only. These results suggest evidence that p110α mediates esophageal inflammation and that PIK-75 has an anti-inflammatory effect by reducing proinflammatory cytokines on feline esophageal epithelial cultured cells.